Determinant of Malaria Reinfection - Muhamad Sahiddin; Zeth Roberth Felle (Science Midwifery, 2022)
Malaria reinfection is one of the concerns in the management of malaria in endemic areas. This study aims to determine the factors that influence the incidence of malaria reinfection. The study used an analytical observational approach with a cross-sectional study design which was conducted in Mei-June 2021 in Keerom Regency, Papua. The research sample amounted to 127 respondents who were selected using simple random sampling technique. Data analysis used fisher's exact test with a significance level of 0.05. The results showed that there was an effect of using mosquito repellent (p = 0.001), the habit of hanging clothes (p = 0.046) and the presence of standing water (p = 0.042) on the incidence of malaria reinfection. Meanwhile, adherence to taking malaria medication (p= 0.623), habit of going out (p= 0.441), habit of using mosquito nets (p= 1,000) and the presence of mosquito netting (p= 0.706) did not affect the incidence of malaria reinfection. It is necessary to conduct health education about the use of mosquito repellent, the habit of hanging clothes and intervention in the community's living environment.